Critical role played by thyroid hormone in induction of neoplastic transformation by chemical carcinogens in tissue culture. - Borek, C (1983)
Incubation of primary cultures of hamster embryo cells (HEC) or mouse fibroblasts (C3H/10T1/2 cells) in media depleted of thyroid hormones does not alter cell growth or survival but renders the cells resistant to neoplastic transformation by benzo[a]pyrene (B[a]P) or N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), carcinogens which yield transformation rates of 10(-4)-10(-2) in media supplemented with triiodothyronine (T3). In C3H/10T1/2 cells, the times of addition or removal of the hormone indicate that T3 exerts maximum effect when added 12 hr prior to treatment with B[a]P and that the progression of transformation from the time of initiation by the carcinogen to full expression and the appearance of transformed foci was independent of the presence or absence of the hormone in the medium. Dependence of transformation on T3 concentration in the medium was observed over the physiological range of 1 pM to 100 nM in C3H/10T1/2 cells treated with B[a]P. These results were similar to our previous findings on the T3 dose-related induction of radiogenic transformation and of Na+,K+-ATPase activity. The latter effect was used as a measure of T3 induction of protein synthesis. A further indication of the potential involvement of protein synthesis in T3 action is the suppression of T3- and B[a]P-dependent transformation by cycloheximide at concentrations that inhibit protein synthesis by approximately equal to 50% in the C3H/10T1/2 cells. We suggest that thyroid hormone induces the synthesis of a host protein that plays a key role in neoplastic transformation by direct-acting chemical carcinogens and by those requiring metabolic activation. In our previous studies, similar T3-dependent mechanisms were implicated in radiogenic transformations.